Identification of apple cultivars hypoallergenic for birch pollen‐allergic individuals by a multidisciplinary in vitro and in vivo approach. Issue 8 (26th August 2022) - Strobl, Maria R.; Vollmann, Ute; Eckl‐Dorna, Julia; Radakovics, Astrid; Ibl, Verena; Schnurer, Madeleine; Brenner, Martin; Dermendjiev, Georgi; Weckwerth, Wolfram; Neumüller, Michael; Frommlet, Florian; Demir, Hilal; et al.
Abstract: Background: Birch pollen‐related apple allergy is the most frequent IgE‐mediated food allergy in Central‐Northern Europe with Mal d 1 as major allergen. Its concentration in apples varies with the cultivar and storage time. Year‐round appealing, hypoallergenic cultivars still are needed to satisfy the nutritional needs of affected individuals. We characterized three promising cultivars by multidisciplinary in vitro assays including long‐term storage and by clinical challenges of allergic individuals before and after the birch pollen season. Methods: Proteins were extracted from fruits of 'Santana', 'Golden Delicious' (GD), and three genuine cultivars in November 2018 and April 2019. Mal d 1‐levels were analysed by mass spectrometry, SDS‐PAGE, immunoblotting, competitive ELISA, and basophil activation tests. Twenty‐eight allergic individuals underwent single‐blinded open food challenges and skin testing with the cultivars and birch pollen in November 2018 and May 2019. Allergen‐specific IgE‐levels were determined. Results: After storage all cultivars except 'Santana' were of appealing appearance and taste. Their Mal d 1 content had increased, also reflected by significantly amplified basophil activation and stronger reactions in clinical challenges. Besides, individuals showed boosted reactivity after pollen exposure indicated by enhanced allergen‐specific IgE‐levels and skin reactions to birch pollen. Still, all cultivars remained significantly less allergenic than GD and comparable to Santana in November 2018 in all assessments except for skin testing. Conclusions: Combined expertise in pomology and allergology identified promising new cultivars for allergic consumers. The evaluation of hypoallergenic apples should incorporate long‐term storage and birch pollen exposure. Basophil activation tests may be suitable in the selection of promising cultivars for oral challenges.